Association of caspase 8 promoter variants and haplotypes with the risk of breast cancer and its molecular profile in an Iranian population: A case‐control study. Issue 10 (30th June 2019) - Bagherabad, Matineh Barati; Afzaljavan, Fahimeh; Vahednia, Elham; Rivandi, Mahdi; Vakili, Fatemeh; Sadr, Susan Sadat Hashemi; Shandiz, Fatemeh Homaei; Pasdar, Alireza
Abstract: Caspase 8 ( CASP8 ) gene plays a key role in the regulation of apoptotic cell death. Expression variation in this gene has been associated with the risk of breast cancer. The aim of this study was to investigate the association of rs3834129 and rs3769821, as functional variants, and their haplotypes with molecular profile as well as the risk of breast cancer in an Iranian population. A case‐control study was conducted on 812 participants including 293 breast cancer patients and 519 healthy controls. Genotyping was performed by polymerase chain reaction–based methods. Statistical analysis was performed using SPSS Ver16. The association between polymorphisms and haplotypes with the risk of breast cancer was estimated by calculating odds ratios (OR) and chi‐square ( χ 2 ) tests. In comparison with ins allele (I) of rs3834129, carriers of del allele (D) showed a lower risk of breast cancer (OR, 0.65; 95% confidence interval [CI], 0.49‐0.87; P = 0.004). The multivariate logistic regression model indicated DD genotype as an independent factor for a decreased risk of breast cancer in our population (OR, 0.18; 95% CI, 0.06‐0.58; P = 0.004). Also, the C allele of rs3769821 was associated with a 43% increased risk of breast cancer ( P = 0.005); however, after adjustment for confounding factors, no association with rs3769821 and breast cancer was observed. In addition, D‐T haplotype and diplotype presented protective effects ( P < 0.05). Our results indicate that genetic variations in the promoter region of CASP8 gene, especially rs3834129, may serve as a genetic risk factor for breast cancer in an Iranian population.